KESETARAAN GENDER DI DESA SUCI PANTI: CAPAIAN SUSTAINABLE DEVELOPMENT GOALS DAN TANTANGAN KULTURAL - Rahma Rina Wijayanti; Oryza Ardhiarisca; Dessy Putri Andini; Avisenna Harkat; Adelia Eka Puspita Ansori; Muhammad Hanip; Siti Anisa (Jurnal Akuntansi dan Ekonomi Bisnis, 2026)
Gender equality is one of the main issues in achieving the Sustainable Development Goals (SDGs), especially in the fifth goal which emphasizes the importance of women's empowerment and equal rights between men and women. This study aims to understand gender equality in Suci Village, Panti District, Jember Regency which has been realized in various aspects such as education, health, economy, and social participation. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that gender equality in Panti Suci Village has shown significant progress through the presence of the Women's Coalition, increased access to education and health, and the involvement of women in productive economic activities. However, patriarchal cultural challenges remain an obstacle that needs to be overcome to achieve more substantial equality.